PENGARUH PENAMBAHAN PURE TERUNG BELANDA (Solanum betacea Cav.) DENGAN GULA TERHADAP MUTU FISIK DAN KIMIA ES KRIM: (Effect of Puree Terung Belanda (Solanum betaceum Cav.) with Sugar on Physical Quality and Chemicals of Ice Cream) - Nurlailah Abdullah; Zainal Zainal; Nurmadiah Nurmadiah (jurnal1, 2018)
Ice cream is one of dairy products in the form of semi-frozen. This research utilizes terung belanda (Solanum betaceum Cav.) to increase the nutritional value of ice cream products. The purpose of this research was to get the best formulation between the addition of puree terung belanda (Solanum betaceum Cav.) with addition of sugar on ice cream making, knowing the physical characteristics (overrun and melting time) as well as chemical characteristics (fat content, protein content, fiber content, total acids and anthocyanins) ice cream, and determine the acceptability of ice cream through the sensory properties (color, aroma, flavor and texture). This study used the method Completely Randomized Design (RAL) descriptively quantitative with 3 replicates with 35% puree terung belanda + 15% sugar + 50% additional ingredients (A1), 30% puree terung belanda + 20% sugar + 50% additional ingredients (A2), and 25% puree terung belanda + 25% sugar + 50% additional ingredients (A3). The results show that the best formulation based on sensory properties is treatment of addition of 30% puree terung belanda + 20% sugar + 50% additional ingredients. Based on the results of statistical analysis showed that the addition of terung belanda (Solanum betaceum Cav.) on ice cream making a real effect on the level of 5% against the value of overrun, melting time, fiber content, anthocyanin levels, and total acid, but no significant effect on the increase of protein content and fat content.